Ontology-based representation of tolerancing and design knowledge for an automated tolerance specification of product concepts - Götz, Stefan; Schleich, Benjamin (Procedia CIRP, 2020)
Motivated by the high importance of the tolerance specification, numerous partially automated approaches have emerged. However, since these approaches require an extensive geometry definition, they are not applicable for an early definition of the tolerance concept and its evaluation by Robust Design aspects. Motivated by this lack, this paper presents a novel ontology-based approach combining knowledge from the product design and tolerancing domains to enable an automated tolerance specification of product concepts. This close linkage enables a more precise specification and bridges the gap to the subsequent final specification in accordance with current GPS standards. Finally, this novel approach is demonstrated by means of a crank drive mechanism.<br
Keywords: Robust Design; Tolerance Specification; Ontology